PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN KARAKTERISTIK PEKERJAAN TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) DENGAN KOMITMEN ORGANISASIONAL SEBAGAI VARIABEL INTERVENING (Studi pada PT Indonesia Comnets Plus Regional Kalimantan) - utin devika (Universitas Tanjungpura, 2020)
Employees as human resources in an organization is the most important asset in a company which is one indicator of success to achieve organizational goals. Matters relating to the achievement of organizational goals cannot be separated from the important role of organizational citizenship behavior (OCB) contributing to the survival of the organization. In addition, organizational commitment and work characteristics of human resources can encourage the creation of organizational citizenship behavior (OCB), of course, determining the success of an organization. Other important factors such as the role of leaders who have a transformational leadership style that encourages human resources in the company to continue to be productive so as to grow organizational citizenship behavior (OCB) for all employees in the company. This research is an explanatory research (Explanatory Research) with quantitative descriptive research. This research is a survey research using a questionnaire through google docs to the employees of PT. Indonesia Comnet Plus Regional Kalimantan with 62 employees. The analytical method used in the hypothesis is path analysis. The results of this study indicate that transformational leadership style does not significantly influence organizational commitment, job characteristics significantly influence organizational commitment, transformational leadership style and job characteristics do not significantly influence Organizational Citizenship Behavior (OCB), and organizational commitment significantly influence Organizational Citizenship Behavior (OCB) OCB) emipiris study on employees of PT Indonesia Comnet Plus Regional Kalimantan.Keywords : Transformational Leadership Style, Job Characteristics, Organizational Commitment, Organizational Citizenship Behavior (OCB)